2001
DOI: 10.1348/014466501163904
|View full text |Cite
|
Sign up to set email alerts
|

Normative data for the HADS from a large non‐clinical sample

Abstract: The present normative data allow clinicians to assess the rarity of a given HADS score, and thus provide a useful supplement to existing cut-off scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

68
571
23
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 715 publications
(689 citation statements)
references
References 4 publications
68
571
23
10
Order By: Relevance
“…Although maternal psychological health in the present study was within a normal range for a community sample (see, Condon & Corkindale, 1998;Crawford, Henry, Crombie & Taylor, 2001;Davies et al, 2008;Jones et al, 2013;Tennant et al, 2007), maternal mood was negatively correlated with perceived mother-infant attachment (see also Davies et al, 2008). This correlation suggests that perceived mother-infant attachment might be a more appropriate measure of the mother-infant relationship than maternal perceptions of their infant's warmth and invasiveness used by Jones et al, (2013).…”
Section: Discussionmentioning
confidence: 50%
“…Although maternal psychological health in the present study was within a normal range for a community sample (see, Condon & Corkindale, 1998;Crawford, Henry, Crombie & Taylor, 2001;Davies et al, 2008;Jones et al, 2013;Tennant et al, 2007), maternal mood was negatively correlated with perceived mother-infant attachment (see also Davies et al, 2008). This correlation suggests that perceived mother-infant attachment might be a more appropriate measure of the mother-infant relationship than maternal perceptions of their infant's warmth and invasiveness used by Jones et al, (2013).…”
Section: Discussionmentioning
confidence: 50%
“…Similarly, the mean Anxiety score for the sample corresponded to the 84 th and 91 st percentile rank for Scottish females and males respectively (Crawford et al, 2001). It seems therefore that the study succeeded in recruiting individuals experiencing elevated levels of emotional dysfunction.…”
Section: Discussionmentioning
confidence: 80%
“…The mean HADS Depression subscale score for the sample corresponded to the 90 th and 94 th percentile ranks for Scottish females and males respectively (Crawford et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the concept of work ability can be defi ned as the ability of a worker to perform his/her job, taking into account the specifi c work demands and mental resources. 20 The questionnaire also included the questions from the HADS (Hospital Anxiety and Depression Scale) questionnaire, 21 a validated questionnaire consisting of 14 items and yielding two measures, one for anxiety and one for depression. Scores on both scales can range between 0 and 21.…”
Section: The Questionnairementioning
confidence: 99%
“…A largescale (n = 1,792) normative study carried out on a non-clinical sample of the UK population found an average score of 6.14 for anxiety and 3.68 for depression. 21 to take part in a telephone interview. The data from the completed questionnaires were collated and analysed.…”
Section: The Questionnairementioning
confidence: 99%